Alcohol consumption and psoriasis: a systematic literature review. (11th July 2013) - Brenaut, E.; Horreau, C.; Pouplard, C.; Barnetche, T.; Paul, C.; Richard, M.‐A.; Joly, P.; Le Maître, M.; Aractingi, S.; Aubin, F.; Cribier, B.; Jullien, D.; et al.
Abstract: The association between alcohol consumption and psoriasis has been frequently discussed since the 1980s, but no systematic review has been elaborated on the subject so far. The aim of this systematic literature review was to assess whether alcohol consumption is more prevalent in psoriasis patients than in the general population and whether alcohol consumption is a risk factor of psoriasis. A systematic literature search was carried out in the Medline, Embase and Cochrane databases using the keywords 'psoriasis' AND 'alcohol drinking' OR 'alcohol‐related disorders'. The search was then enlarged with the keywords 'psoriasis' AND 'risk factor' OR 'comorbidity'. Altogether 911 references in English and French were found. Out of these, 837 articles were excluded by reading the abstract and 46 by reading the article. A total of 28 articles were selected. Alcohol consumption in psoriasis patients versus the general population: 23 studies were selected; 18 concluded that alcohol consumption was more prevalent in psoriasis patients, and 5 did not. Three studies compared the prevalence of excessive drinking using a questionnaire on alcohol dependence (CAGE or Self‐administered alcohol screening test (SAAST)) or with quantitative criteria for excessive drinking. In these studies, excessive drinking was more prevalent among psoriasis patients than in the general population. Other articles studied the quantity and type of alcohol consumed. In 11 studies, psoriasis patients consumed more alcohol than the controls. Four other studies showed excessive alcohol consumption in psoriasis patients without control group comparison. Conversely, five studies identified no difference in alcohol consumption between psoriasis patients and the general population. The heterogeneity in the measurement of alcohol consumption did not allow performing meta‐analysis. Alcohol as a risk factor for psoriasis: only five studies were selected. In four of these studies alcohol was found to be a risk factor for psoriasis. Alcohol consumption seems to be greater in psoriasis patients than in the general population. However, there is not enough evidence to establish whether alcohol consumption is indeed a risk factor for psoriasis.